Additive Manufacturable Materials for Electrochemical Biosensor Electrodes. (16th December 2020) - Elbadawi, Moe; Ong, Jun Jie; Pollard, Thomas D.; Gaisford, Simon; Basit, Abdul W.
Abstract: With the impending Industrial Revolution 4.0, the information produced by sensors will be central in many applications. This includes the healthcare sector, where affordable healthcare and precision medicine are highly sought after. Electrochemical sensors have the potential to produce affordable, high sensitivity and specificity, intuitive, and rapid point‐of‐care diagnostics. Underpinning these achievements is the choice of material and the fabrication thereof. In this review, the different types of materials used in electrochemical biosensors are reported, with a focus on synthetic conductive materials. The review demonstrates that there is an abundance of materials to select from, and compositing different types of materials further widens their applicability in biosensors. In addition, the fabrication of such materials using the state‐of‐the‐art of fabrication technology, additive manufacturing (AM), is also detailed. The need for compositing is evident in AM, as the feedstock for certain AM technologies is inherently nonconductive. Both material choice and fabrication technologies limitations are also discussed to highlight opportunities for growth. The review highlights how recent technological advancements have the potential to drive the healthcare industry toward achieving its primary goals. Abstract : Electrochemical biosensors (ECBs) are a versatile sensing technology, capable of detecting a myriad of chemicals. ECBs are also well‐positioned for point‐of‐care diagnostics. Recently, there has been growing interest to fabricate ECB electrodes via additive manufacturing (AM). The progress report provides an updated overview of the materials and designs of ECBs fabricated via AM.